2017
DOI: 10.1515/jpem-2016-0170
|View full text |Cite
|
Sign up to set email alerts
|

The association between obesity, hypertension and left ventricular mass in adolescents

Abstract: Obesity is a risk factor for LVH independent of HT. To identify masked HT, 24-h ABPM and cardiac examination should be routinely performed in obese adolescents. Using a limit of LVMI ≥38 g/m2.7 in evaluating LVH secondary to HT in obese individuals may lead to an overestimated diagnosis rate of LVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…Previous studies utilizing ABPM in obese children have shown the prevalence of ambulatory hypertension ranging from 20% to as high as 60% (5,6,17). The severity of hypertension increased with an increasing BMI in the present study, which is in concordance with previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies utilizing ABPM in obese children have shown the prevalence of ambulatory hypertension ranging from 20% to as high as 60% (5,6,17). The severity of hypertension increased with an increasing BMI in the present study, which is in concordance with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Obese children with ABPM have shown a prevalence for ambulatory hypertension ranging from 25% to as high as 48.6% in previous studies (5,6) with 20% having severe ambulatory hypertension. It has been postulated previously that ambulatory systolic blood pressure and obesity are independently associated with left ventricular hypertrophic remodeling in children (7).…”
Section: Introductionmentioning
confidence: 90%
“…There are not much well-established data for the correlation of LVMI with obese and hypertensive children yet. Dibeklioglu et al [40] reported that the most predictive values associated with LVMI in obese adolescents are 24-h mean SBP, and 24-h SBP load, daytime SBP load, nighttime SBP load and 24-h SBP, similar to our results. However, in normal weight-hypertensive adolescents, 24-h mean DBP, daytime diastolic load, daytime DBP index, daytime SBP index, nighttime systolic loading and nighttime DBP index were found to be predictors of the LVMI.…”
Section: Discussionsupporting
confidence: 92%
“…In research by Huang et al [5], obese patients had larger LAD, LAA, and LAV, both in univariate and multivariate analysis. Dibeklioglu et al [19] showed that obesity in children was a risk factor for LV hypertrophy independent of hypertension, and Kurisu et al [20] found an influence of BMI on the correlations between LVM and ECG indices used in the diagnosis of LV hypertrophy, such as the Cornell product and Sokolow-Lyon indices.…”
Section: Discussionmentioning
confidence: 99%